A preventative approach to promote food safety: bacterial contamination of domestic refrigerators. Issue 8 (1st August 2016) - Esfarjani, Fatemeh; Khaksar, Ramin; Mohammadi Nasrabadi, Fatemeh; Roustaee, Roshanak; Alikhanian, Haleh; Khalaji, Niloofar; Mousavi Khaneghah, Amin; Hosseini, Hedayat
Abstract : Purpose: Domestic refrigerators could be considered as one of the major potential sources of food-borne diseases, in addition limited data are available regarding the level of contamination of domestic refrigerators in Iran. The purpose of the present study was to detect some of bacterial contamination in domestic refrigerators. Design/methodology/approach: One hundred and four households were randomly selected from 10 health centers in five areas of Tehran, Iran. Visual inspection and temperature evaluation of the households' refrigerators were done. In addition, the refrigerators were swabbed and analyzed for contaminants using polymerase chain reaction (PCR) method. DNA was isolated and purified by the proposed standard protocol. Findings: Screening of the domestic refrigerators by PCR method showed that 51.7% of the samples were positive for pathogens as follows: L. monocytogenes 41.6%, S. aureus 5.5%, Salmonella spp 4.6%, and E. coli O157:H7 0%; consequently, non of mentioned pathogens were detected in 48.3% of the refrigerators. Results of the visual inspection indicated that 57% of the refrigerators were on desirable, 36.5% were acceptable, and 7% were weak conditions. Most of the refrigerators about (44%) had desirable temperatures. There were no significant correlations between the visual inspection scores, temperature and frequency of isolation of specific pathogens in the domestic refrigerators. A significant correlation was observed between contamination and education of parents (P<0.05). Originality/value: Determination of the bacterial contamination and evaluating the temperature of domestic refrigerators in Iran can be considered as a novel approach of current study. These findings could be employed in designing and implementing appropriate educational interventions to promote food safety and diminish the risk of food-borne illnesses. Also obtained results might be applied as introduction for further investigations.